Laying Performance, Egg Characteristics and Egg Compositions in Thai Indigenous Hens - Kreingkrai C.; Intr S.; Katuhide T. (1998)
Experiment one: One hundred and ten Thai indigenous pullets, 21 weeks of age, kept in individual cages under a photoperiod of 14 hour light: 10 hour darkness, were used to study laying performance until 60 weeks of age. Age and body weight were 158 days and 1.49 kg respectively at the onset of laying. Egg production rose gradually from 21 to 45 weeks of age and increased sharply to peak at 47 weeks of age (73.4% production), decreased sharply and then gradually declined. Cumulative egg production was 113.7 eggs/hen or 41.1% hen-day production on average. Feed conversion rate was, on average, 6.1 kg/kg of eggs which was highest in the first four weeks and lowest from 45-48 weeks of age. Ninety-two point three percent of eggs weighed less than 55 g. the total mortality rate of hens in this experiment was 28.2 %. Experiment two: Fifty female Thai indigenous hens, 52 weeks of age and reared under the same condition as experiment one, were used to examine egg characteristics of egg compositions. The average egg weight was 49.8 g, 5.4 cm. In length, 4.1 cm. In width and 132.2 for egg shape index. There were differences (p<0.05-0.01) in egg length and egg width between egg sizes but was not significantly different in egg shape. Egg weight was positively regressed (p<0.01) and correlated (p<0.01) to egg width and egg length, but not for egg shape index. The mean specific gravity was 1.0888. It was negatively regressed (p<0.01) and correlated (p<0.10) to egg weight but was positively regressed (p<0.01) and correlated (p<0.01) to egg shell percentage. Thai indigenous chickens egg contained 31.5% yolk, 58.9% albumen and 9.6 shell and shell membrane. All of them were differences (P<0.05-0.01) among egg sizes. Albumen and shell weight were positively regressed (p<0.01) but yolk was a negatively regressed and both were correlated (P<0.01) to egg weight. The percentage of egg compositions between yolk x albumen and albumen x shell were negatively regressed (P<0.01) and were correlated (p<0.01).